The Duchy of Philippopolis (1204–c. 1236/37): A Latin Border Principality in a Byzantine (Greek/Bulgarian) Milieu. (31st December 2022) - Van Tricht, Filip
Abstract: The duchy of Philippopolis was created after the crusader conquest of Constantinople in 1204. Ruled by members of the Trith and Estreux families, local lords from the county of Hainaut in the Low Countries, this little-studied principality lasted for several decades, possibly until the mid-1230s. Bordering the Bulgarian kingdom/empire, the region suffered the consequences of successive military campaigns during the early years of its existence. Following Emperor Henry's victory at Philippopolis in 1208 against Tsar Boril and the concomitant Latin-Bulgarian peace and alliance in 1213, a more tranquil and harmonious period ensued. While a lack of sources prevents a detailed analysis, a number of hypotheses can be formulated regarding various aspects, such as the secular and ecclesiastical organization of the principality, the cohabitation of Latins and local Greeks and Bulgarians, and the relationship with other major players in Latin Romania including the Latin Emperor, the city of Venice, and the neighbouring lord of the Rhodope region, despot Alexios Sthlabos.